Stress relaxation of selected viscoelastic herbs - Yusof, Yus Aniza; Mohd Din, S. N.; Chin, Nyuk Ling; Anuar, Mohd Shamsul (Malaysian Tribology Society, 2011)
This study presents stress relaxation characteristics of selected viscoelastic herbs which are Andrographis paniculata, Orthosiphon stamineus, and Eurycoma longifolia Jack. These herbs can be found in the Asia region and have been reported on having several therapeutics properties. The herbs powders were compressed into tablets, which is convenient for consumption and packaging. A uniaxial die of 13mm in diameter was used using a universal testing machine with pressures ranging from 15 to 30 MPa and the compression speeds between 3mm/min and 6mm/min. The stress relaxation characteristics and related parameters were compared. The Eurycoma l. Jack showed plastic deformation, however the value of the asymptotic residual modulus indicate that the deformation was insignificant to form a coherent tablet. Binder is suggested to be added to the compression process. Thus, these properties are essential to understand storage and transportation of herbal tablets.